Exploring the efficacy of pre-service teachers as makers of virtual language/culture learning environments - Sabrina Priego; Meei-Ling Liaw (University of Groningen Press, 2021)
Previous literature in the area of computer assisted language learning in Second/Foreign Language (L2/FL) education has highlighted the benefits of using virtual environments for learning the target language and culture (e.g. Blyth, 2018; Lloyd, Rogerson, & Stead, 2017; Shih, 2015). In addition, a number of researchers have demonstrated that one of the important attributes of virtual environments for language learning is the affordances of physical and social presence (e.g. Cho, Yim, & Paik, 2015; McKerlich, Riis, Anderson, & Eastman, 2011; Peterson, 2011; Wang, Lawless-Reljic, Davies, & Callaghan, 2011). However, to our knowledge, no previous studies have investigated the affordances of virtual environments from the makers' point of view. In this present study, 22 Canadian pre-service teachers used a 360 degree camera and Virtual Reality (VR) software to construct VR environments that were used as cultural virtual tours. They then invited 24 Taiwanese students to interact with them in their created immersive environments. Analyses of the pre-service teachers' final written reflections showed that most of them reported that they experienced a sense of physical and social presence in their self-created VR environments and that they enjoyed participating in the VR project. However, various factors, such as the design of the task, technical difficulties with the VR equipment, and limits of the social VR network were also found to have negatively influenced their satisfaction with the VR experience. Findings from this study might inform other L2/FL teachers who design VR environments and integrate social VR in their classes. Suggestions for future research are also provided.